The Determinants in The Adoption of Banking Application Technology - Deby Yuliana Wahyudi; Nur Khusniyah Indrawati; Nanang Suryadi (AKRUAL: JURNAL AKUNTANSI, 2025)
Introduction/Main Objectives: This study aims to examine the influence of perceived ease of use and perceived usefulness on the continuance intention of Wondr by BNI application users, with trust and satisfaction as mediating variables. Background Problems: Sustainable use for mobile banking service providers is important because retaining existing users is an important source of competitive advantage. Novelty: This study proves that the intention to continue using mobile banking is driven by perceptions of ease of use and perceived usefulness. Research Methods: This study is an explanatory study using a quantitative approach. The research population is Wondr by BNI users in Indonesia. This study uses purposive sampling technique. Data collection was conducted through a survey of 400 Wondr by BNI users. Data were analyzed using descriptive statistical methods and SEM-PLS. Finding/Results: Perceived ease of use and perceived usefulness have a direct and significant effect on each variable, trust, satisfaction, and the continuance intention of Wondr by BNI users. Additionally, satisfaction acts as a partial mediator in the relationship between perceived usefulness and continuance intention. Conclusion: Based on these findings, it is recommended that Wondr by BNI improve ease of use and usefulness to enhance user satisfaction and encourage continuance intention for Wondr by BNI. This study expands the development of the Technology Acceptance Model (TAM) by incorporating trust and satisfaction factors in analyzing the continuance intention of Wondr by BNI users. This study contributes to the implementation of mobile banking, particularly Wondr by BNI in Indonesia.